2016
DOI: 10.4049/jimmunol.1501989
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Damage Response Regulates RAG1/2 Expression in Pre–B Cells through ATM-FOXO1 Signaling

Abstract: The recombination activating gene (RAG) 1 and RAG2 protein complex introduces DNA breaks at Tcr and Ig gene segments that are required for V(D)J recombination in developing lymphocytes. Proper regulation of RAG1/2 expression safeguards the ordered assembly of Ag receptors and the development of lymphocytes, while minimizing the risk for collateral damage. The ataxia telangiectasia mutated (ATM) kinase is involved in the repair of RAG1/2-mediated DNA breaks and prevents their propagation. The simultaneous occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 62 publications
3
29
0
Order By: Relevance
“…Previous studies reported that the Rag1 and Rag2 proteins each have a half-life of ~10–12 minutes (29, 47, 48). Considering these reports and our observed kinetics and extents of Rag1 and Rag2 mRNA loss in response to IR, one would predict appreciable decreased levels of Rag1 and Rag2 protein at 1 hour after irradiation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies reported that the Rag1 and Rag2 proteins each have a half-life of ~10–12 minutes (29, 47, 48). Considering these reports and our observed kinetics and extents of Rag1 and Rag2 mRNA loss in response to IR, one would predict appreciable decreased levels of Rag1 and Rag2 protein at 1 hour after irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…While we were preparing this manuscript, the Guikema lab reported that the DDR response regulates Rag1/Rag2 expression in pre-B cells through ATM-FOXO1 signaling (29). They showed that the genotoxic drug NCS caused rapid downmodulation of Rag1 and Rag2 mRNA and Rag1 protein (they did not report on Rag2 protein) in STI571-treated human BCR-ABL + pre-B cell lines (BV173 and SUP-B15) and mouse v-Abl transformed pro-B cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations